Highly enantioselective copper-catalyzed alkylation of β-ketoesters and subsequent cyclization to spirolactones/bi-spirolactones - Deng, Qing-Hai; Wadepohl, Hubert; Gade, Lutz H. (Journal of the American Chemical Society, 2012)
Cu-catalyzed enantioselective alkylation of β-ketoesters using alcohols for in situ preparation of alkylating reagents is reported. A number of functionalized β-ketoesters containing a quaternary carbon stereocenter are obtained with up to 99% ee. The alkylation products derived from 2-substituted allylic alcohols or their corresponding iodides can then be converted to spirolactones, bi-spirolactones, and related chiral target products.